(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Autoimmune cell activation causes damage to different cells of the human body. In rare cases, this autoimmune cell activation destroys the Myelin sheath which wraps around the long nerve cell bodies and leads to the development of extremely rare nerve cell-related autoimmune disorder known as Guillain-Barre syndrome. The present case of 34 years old male patient who was admitted in the general medicine department of a tertiary care teaching hospital with complaints of arthralgia, generalized weakness mediated with tingling sensation started at feet progressing upwards. Treatment included antibacterial agents and steroidal autoinflammatory agents. After the continuous treatment for a period of 13 days, the patient was found to be normal with no major complaints and so, the pharmacist when performed discharge counseling and patient was discharged with a 2-week drug regimen after discharge.